2019
DOI: 10.1093/cdn/nzz033.or26-08-19
|View full text |Cite
|
Sign up to set email alerts
|

Sonication and Short-term Incubation Alter the Content of Bovine Milk Exosome Cargos and Exosome Bioavailability (OR26-08-19)

Abstract: Objectives Exosomes are endogenous nanoparticles that participate in cell-to-cell communication through the transfer of cargos such RNAs, lipids and proteins from donor cells to recipient cells. Previously, we showed that mammals absorb exosomes from milk. Ultrasonication causes a transient disruption of the exosome membranes, leading to loss of microRNAs. When mice were fed diets based on the AIN-93G formulation, modified to contain a physiological amount of milk exosomes (exosome and RNA-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The sonication method is useful for encapsulating lipophilic and hydrophilic drugs because the vibrations disrupt the membranes and facilitate entry. However, this method is only applicable for small molecules and might cause the adhesion of the molecule to the EV surface, which could change the biodistribution and release of the drug [19,47]. On the other hand, direct incubation is one of the simplest techniques and usually does not require the addition of any additional reagents; however, it is also limited to small and generally lipophilic compounds [19,46].…”
Section: Evs For Drug Deliverymentioning
confidence: 99%
“…The sonication method is useful for encapsulating lipophilic and hydrophilic drugs because the vibrations disrupt the membranes and facilitate entry. However, this method is only applicable for small molecules and might cause the adhesion of the molecule to the EV surface, which could change the biodistribution and release of the drug [19,47]. On the other hand, direct incubation is one of the simplest techniques and usually does not require the addition of any additional reagents; however, it is also limited to small and generally lipophilic compounds [19,46].…”
Section: Evs For Drug Deliverymentioning
confidence: 99%
“…We first assessed that how these nine included studies conducted the diagnostic experiment using exosomal biomarkers. According to previous studies we found that, the method of exosome extraction, RNA profiling, and analyzing could affect the results of diagnostic evaluation [51][52][53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Electroporation is a well-established technology in cell labeling for cell engineering and imaging, and encapsulating nucleotides into liposomes for gene therapy. However, this strategy decreases membrane integrity, requires removal of free label, and causes aggregation of loaded particles as well, which reduces the subsequent yield and can lead to false detection in off-target organs such as the liver and kidneys due to the amount of loaded agents leaked from the vesicle in vivo [18,62] .…”
Section: Electroporationmentioning
confidence: 99%